Demanda do serviço de saúde de emergência: características e fatores de risco para o uso inadequado - Carret, Maria Laura Vidal (2007)
This study evaluated the demand of emergency health service. It was performed a descriptive analyses of 1647 adults that consulted at emergency public service of Pelotas, Brazil. Older subjects, with non white skin color, lower schooling, without partner, and smokers presented higher prevalence of consultations at this service when compared with the general population. Individuals waited, on average, 15 minutes to have their consultations, exams were requested in more than 40% of the visits, and intravenous medication were administered in one third of the visits. Elderly waited longer before searching the service, but they had lowest awaiting time after arriving at emergency service and had highest percentage of regular doctor and social support. Elderly had more diagnosis related to circulatory system, while among the youngest, external causes were the most frequent. Conclusion: The low waiting average for consultation suggest this service provide an immediate care while the great number of ill-defined signs or symptoms indicate that the provided care is provisional. It is necessary to train emergency professionals to reduce the number of tests requested and to assure that either professional as the population is conscious about the importance of a continuity of care.